Augmented reality application to museum visitor experiences - Hassan, A.; Ramkissoon, Haywantee (2017)
This chapter draws attention to the use of innovative technologies in visitor management, specifically in managing visitor experiences. It aims to replicate cited examples of augmented reality (AR) application in museums in developed countries in the context of Bangladesh, an emerging tourist destination. Bangladesh has distinctive features encompassing history and culture, suggesting that AR can assist in the implementation and promotion of cultural tourism through activities in museums. The study's exploratory findings suggest that AR may be applied to museums such as the Bangladesh National Museum given adequate infrastructure.